Type-1 astrocyte-like stem cells harboring Cacna1d gene deletion exhibit reduced proliferation and decreased neuronal fate choice - Völkening, Bianca; Schönig, Kai; Kronenberg, Golo D.; Bartsch, Dusan; Weber, Tillmann (Hippocampus, 2018)
In the central nervous system, CaV1.2 and CaV1.3 constitute the main L-type voltage-gated calcium channels (LTCCs) coupling membrane depolarization to gene transcription. We have previously demonstrated that inducible disruption of Cav1.2 in type-1 astrocyte-like stem cells of the adult dentate gyrus (DG) impairs hippocampal neurogenesis in a cell-autonomous fashion. To address the role of Cav1.3 channels (encoded by the Cacna1d gene), we here generated TgGLAST-CreERT2/Cacna1dfl/fl/RCE:loxP mice which facilitate inducible deletion of Cacna1d in tandem with induction of EGFP expression in type-1 cells, allowing tracking of recombined cells and their descendants. Neurosphere cultures derived from fluorescence-activated cell sorting sorted Cacna1d-deficient (Cacna1d-/-/EGFP) hippocampal neural precursor cells (NPCs) exhibited a significant decrease in proliferative activity. Further, under differentiation conditions, Cacna1d deficiency conferred an increase in astrogenesis at the expense of neurogenesis. In like manner, type-1 cells lacking Cacna1d showed reduced proliferation in the dentate gyrus (DG) in vivo. Moreover, Cacna1d deficiency resulted in a significant decrease in the number of newly born cells adopting a neuronal fate. Finally, massive excitation induced by repeated electroconvulsive seizures rescued the proliferation defect of Cacna1d-/-/EGFP type-1 cells. Together, the effects of Cacna1d gene deletion closely recapitulate our earlier findings on the role of Cav1.2 channels expressed by type-1 cells. Similar to Cav1.2 channels, Cav1.3 channels on type-1 cells boost type-1 cell proliferation and promote subsequent neuronal fate choice.